ANALISIS KUALITAS PELAYANAN, KEMUDAHAN PENGGUNAAN APLIKASI M-BCA TERHADAP KEPUASAN NASABAH PEMBUKAAN REKENING ONLINE - Rahayu, Yola Putri; Widiati, Euis (LPPM STIE YKPN Yogyakarta, 2024)
In the current era of digitalization, business competition is increasing, making service entrepreneurs switch to running their business using digitalization to improve service quality and ease of use. This research aims to determine the effect of service quality and ease of use of the M-BCA application on customer satisfaction when opening an online account. This research uses a quantitative research design. The population in this study was 20.8 million customers (respondents), while the sample size was 100 respondents. The sampling technique used is purposive sampling. The primary data used in this research is a questionnaire survey distributed using Google Form to 100 people who have opened an online account on the M-BCA application. Hypothesis testing uses multiple linear regression analysis and the research results show that service quality and ease of use have a partial or simultaneous positive influence on customer satisfaction.